Genetic Variants and Protein Alterations of Selenium- and T-2 Toxin-Responsive Genes Are Associated With Chondrocytic Damage in Endemic Osteoarthropathy - Ning, Yujie; Hu, Minhan; Diao, Jiayu; Gong, Yi; Huang, Ruitian; Chen, Sijie; Zhang, Feiyu; Liu, Yanli; Chen, Feihong; Zhang, Pan; Zhao, Guanghui; Chang, Yanhai; et al. (Frontiers in Genetics, 2022)
The mechanism of environmental factors in Kashin-Beck disease (KBD) remains unknown. We aimed to identify single nucleotide polymorphisms (SNPs) and protein alterations of selenium and T-2 toxin responsive genes to provide new evidence of chondrocytic damage in KBD. This study sampled the cubital venous blood of 258 subjects including sex-matched 129 KBD patients and 129 healthy controls for SNP detection. We applied an additive model, a dominant model, and a recessive model to identify significant SNPs. We then used the Comparative Toxicogenomics Database (CTD) database to select selenium- and T-2 toxin- responsive genes with the candidate SNP loci. Finally, immunohistochemistry was applied to verify the protein expression of candidate genes in knee cartilage obtained from 15 subjects including 5 KBD, 5 osteoarthritis (OA) and 5 healthy controls. Forty-nine SNPs were genotyped in the current study. The C allele of rs6494629 was less frequent in KBD than in the controls (OR=0.63, p=0.011). Based on the CTD database, PPARG, ADAM12, IL6, SMAD3, and TIMP2 were identified to interact with selenium, sodium selenite, and T-2 toxin. KBD was found significantly associated with rs12629751 of PPARG (additive model: OR=0.46, p=0.012; dominant model: OR=0.45, p=0.049; recessive model: OR=0.18, p=0.018) , rs1871054 of ADAM12 (dominant model: OR=2.19, p=0.022), rs1800796 of IL6 (dominant model: OR=0.30, p=0.003), rs6494629 of SMAD3 (additive model: OR=0.65, p=0.019; dominant model: OR=0.52, p=0.012), and rs4789936 of TIMP2 (recessive model: OR=5.90, p=0.024). Immunohistochemistry verified significantly upregulated PPARG, ADAM12, SMAD3 and TIMP2 in KBD compared with OA and normal controls (p<0.05). Genetic polymorphisms of PPARG, ADAM12, SMAD3 and TIMP2 may contribute to the risk of KBD. These genes could promote the pathogenesis of KBD by disturbing ECM homeostasis.